An assessment of the technical-vocational aspects of the non-formal education training programs in the national capital region - Noble, Estefania Casabar; Corpuz, Aurora G. (1991., 1991)
This study was conducted primarily to assess the technical/vocational aspects of the Non-formal Education (NFE) program in some selected areas of the National Capital Region (NCR). Specifically, the aims of the study were to: (1) determine the extent to which graduates were able to get employment related to training after graduation; (2) determine how training has improved personal/family/community living; (3) assess the characteristics of trainors; (4) determine the adequacy of training facilities; (5) assess the effectiveness of the teaching/learning methods used in the training programs; and (6) find out the pressing problems encountered by the respondents. The respondents were 210 trainees/graduates (clientele); 24 administrators/supervisors, 24 teachers/trainors from the public elementary schools offering NFE program in the divisions of Manila, Pasay City, Quezon City, and Kaloocan City. The schools included were selected randomly from the list of schools obtained from the Department of Education, Culture and Sports. Descriptive statistics (mean, standard deviation, percentage and ranking) were used to describe characteristics of respondents. The Spearman rank correlation coefficient was used to determine some relationships between perceptions of administrators/supervisors and trainors or between clientele and supervisors/administrators regarding training facilities, aims of non-formal education program, characteristics of trainors; and effectiveness of teaching learning methods and problems encountered by them. The results of the study showed that: (1) dressmaking ranked first among the jobs held by clientele; (2) only 94 out of the 210 clientele were employed outside their homes and the rest were self-employed; (3) the respondents reported that they had improved their personal/family/community living as a result of their NFE training; (4) teachers/trainors of NFE were generally rated competent, had a mastery of their subject matter; and (5) teaching/learning methods used were appropriate and effective. However, training facilities were rated as inadequate. The pressing problems reported by the respondents were the lack of adequate equipment, facilities, and narrow and poorly ventilated rooms.
Computer print-out (photocopy).
Thesis (Ph.D.Home Economics)--University of the Philippines, Diliman.
Keywords: Non-formal education -- Activity programs; Activity programs in education; Vocational evaluation